Translation of the Decision of the International Court of Justice related to the “Obligation to Negotiate Access to the Pacific Ocean” (Bolivia v. Chile) Preliminary Objection (2016)
Este documento contiene en texto completo el articulo Translation of the Decision of the International Court of Justice related to the “Obligation to Negotiate Access to the Pacific Ocean” (Bolivia v. Chile) Preliminary Objection publicado en ACDI - Anuario Colombiano de Derecho Internacional; Vol. 9 (2016): ACDI; 391-430;Annuaire Colombien de Droit International - ACDI; Vol. 9 (2016): ACDI; 391-430;Colombian Yearbook of International Law - CYIL; Vol. 9 (2016): ACDI; 391-430;2145-4493;2027-1131;10.12804/acdi9.1.2016